2014
DOI: 10.5713/ajas.2014.14223
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sperm Sex Ratio in Bovine Semen Using Multiplex Real-time Polymerase Chain Reaction

Abstract: Gender selection is important in livestock industries; for example, female calves are required in the dairy industry. Sex-sorted semen is commonly used for the production of calves of the desired gender. However, assessment of the sex ratio of the sorted semen is tedious and expensive. In this study, a rapid, cost effective and reliable method for determining the sex ratio was developed using a multiplex real-time polymerase chain reaction (PCR) assay. In this assay, the X and Y chromosome-specific markers, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…; Khamlor et al. ). Here, we modified and optimized an absolute quantification qPCR protocol to measure the proportion of Y‐CBS in the sperm samples of house mice.…”
Section: Methodsmentioning
confidence: 97%
“…; Khamlor et al. ). Here, we modified and optimized an absolute quantification qPCR protocol to measure the proportion of Y‐CBS in the sperm samples of house mice.…”
Section: Methodsmentioning
confidence: 97%
“…Unfortunately, the sex ratio of spermatozoa was not examined before and after the sexing process due to the limited time because this project must be completed in 1 year. Further research is needed to determine sperm sex ratio using polymerase chain reaction as reported by Khamlor et al [42] and its application in a larger recipient population.…”
Section: Discussionmentioning
confidence: 99%
“…Semen-sexing cytometers quantify sex skew using Technical note: Droplet digital PCR precisely and accurately quantifies sex skew in bovine semen the same DNA-binding dye and detection scheme that originally generated the sexed semen, rather than an independent test; the skew data are therefore subject to the same variations or biases as manufacturing the sexskewed product and are limited by the lack of unique, positive identifiers for the X and Y chromosomes. The FISH and qPCR approaches both specifically identify X and Y chromosomes (Kawarasaki et al, 1998;Rens et al, 2001;Habermann et al, 2005;Parati et al, 2006;Puglisi et al, 2006;Khamlor et al, 2014), but lack quantitative sensitivity and statistical rigor due to sampling (FISH) and sensitivity (qPCR) limitations. In an effort to overcome these challenges, we present methods for a droplet digital PCR (ddPCR) sex skew assay that quantifies total X and Y chromosome copies, reporting sex skew as a percentage with a variance of ±0.5 percentage point.…”
Section: Technical Notementioning
confidence: 99%